AN IMPROVED METHOD FOR SHORTENING REGRESSION TEST OPTIMIZATION - O. O, Solanke; B. T, Efuwape; A. I, Taiwo, (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2014)
The primary objective of every software engineering product is unwavering product quality. Extensive testing and product development are required. The emphasis on quality increases as new features are added to any current product. This has a greater impact on the "regression" testing phase, in which all older functionality of the product is checked to ensure that it is still working. If we don't have any regression optimization techniques in place, the product will mature and have more features, making it more difficult to find regression test cases for such a complicated product. Such a circumstance will directly affect the product's delivery and timeline. Consequently, in this research, we offer a novel method for shortening the regression test phase by selecting the suitable subset of the total number of test cases in the big test suite.